Size distribution of Raindrops -Part V (MAUSAM, 1968)
Results of measurements of the size distribution of raindrops for thunderstorm rain recorded at Poona during August, September and October 1956 are described and compared with those for monsoon rain. The basic data are given in the form of a table showing the number of raindrops received per square metre per second, (grouped country at intervals of 0.25 mm in diameter) for various intensities of precipitation. The total momentum and kinetic energy of raindrops per square metre per sea have been determined as a function of the Intensity of precipitation. The concentration of raindrops and liquid water per cubic metre of air and their dictribution in different diameter groups is discussed. The radar reflectivity factor for individual rain periods has been calculated for monsoon as well as thunderstorm rain, Evidence for the breaking up of large raindrops is presented in the paper.